1980
DOI: 10.1056/nejm198010163031601
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Total Coronary Occlusion during the Early Hours of Transmural Myocardial Infarction

Abstract: To define the prevalence of total coronary occlusion in the hours after transmural myocardial infarction, we used coronary arteriography to study the degree of coronary obstruction in 322 patients admitted within 24 hours of infarction. Total coronary occlusion was observed in 110 of 126 patients (87 per cent) who were evaluated within four hours of the onset of symptoms; this proportion decreased significantly, to 37 of 57 (65 per cent), when patients were studied 12 to 24 hours after the onset of symptoms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
652
2
45

Year Published

1985
1985
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,599 publications
(712 citation statements)
references
References 22 publications
13
652
2
45
Order By: Relevance
“…The pioneering angiographic work of DeWood et al (14), published in 1980, first described an acute thrombotic coronary occlusion during the initial hours of myocardial infarction and thus triggered the interest in reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The pioneering angiographic work of DeWood et al (14), published in 1980, first described an acute thrombotic coronary occlusion during the initial hours of myocardial infarction and thus triggered the interest in reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) constitute 6% to 14% of all those with acute myocardial infarction (AMI) 1, 2, 3, 4, 5, 6, 7, 8. Recent evidence demonstrates that patients with MINOCA are distinct from patients with AMI with the classic culprit lesion—namely, >50% plaque‐mediated occlusion of the coronary artery (myocardial infarction due to coronary artery disease [MI‐CAD])—by having lower prevalence of the traditional cardiac risk factors and a lower but clinically significant annual mortality rate 1, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, investigations applying this technique have shown that, in approximately 30% of events with acute myocardial infarction, the infarction-related artery spontaneously reperfuses [3]. This demonstrates that the body has a potent endogenous defence mechanism to protect against formation of occluding arterial thrombi.…”
Section: Introductionmentioning
confidence: 99%